Assessing anxiety in Black men with prostate cancer: Further data on the reliability and validity of the Memorial Anxiety Scale for Prostate Cancer (MAX-PC) - Nelson, Christian J. (Support Care Cancer, 2016)
PURPOSE: The National Cancer Institute has highlighted the need for psychosocial research to focus on Black cancer patients. This applies to Black men with prostate cancer, as there is little systematic research concerning psychological distress in these men. This study was designed to validate the Memorial Anxiety Scale for Prostate Cancer (MAX-PC) in Black men with prostate cancer to help facilitate research within this group. METHODS: At three institutions, Black men with prostate cancer (n=101) completed the MAX-PC, the Hospital Anxiety and Depression Scale (HADS), the Functional Assessment of Cancer Therapy (FACT) Quality of Life Questionnaire, and the Distress Thermometer. RESULTS: The average age of the 101 men was 66 (S.D. = 10) and 58% had early-stage disease. The MAX-PC, and its subscales (Prostate Cancer Anxiety, PSA Anxiety, and Fear of Recurrence), produced strong coefficient alphas (0.89, 0.88, 0.71, and 0.77, respectively). Factor analysis supported the three-factor structure of the scale established in earlier findings. The MAX-PC also demonstrated strong validity. MAX-PC total scores correlated highly with the Anxiety subscale of the HADS (r = 0.59, p < 0.01), and the FACT Emotional Well-Being subscale (r = −0.55, p < 0.01). Demonstrating discriminant validity, the correlation with the HADS Depression Subscale (r = 0.40, p < 0.01) and the CES-D (r = 0.42, p < 0.01) were lower compared to the HADS Anxiety subscale. CONCLUSIONS: The MAX-PC is valid and reliable in Black men with prostate cancer. We hope the validation of this scale in Black men will help facilitate psychosocial research in this group that is disproportionately adversely affected by this cancer.